Active House: Smart Nearly Zero Energy Buildings - Feifer, Lone (PoliMI SpringerBriefs,, 2018)
The book provides an overview of the Active House (AH) vision, intended as a building design method "beyond" the passive approach for buildings of the future that will be more and more connected, smart and innovative. It offers a novel philosophical design approach in which buildings, new or renovated, are in balance with natural, renewable energies and become "concentrators-distributors" of energies instead of being consumers of resources. The book is composed of five chapters, providing information on fundamental aspects of innovations toward resource-efficient buildings, as well as case studies presenting the concept in practice. It demonstrates that a completely new design approach is possible, and that a turning point has been reached. Lastly, it shows how the AH Alliance, along with designers, institutions, industries and academies, is bringing a breath of fresh air to the world of construction.